Strategi Pengembangan Infrastruktur Energi untuk Memperbaiki Aksesibilitas dan Ketersediaan Energi di Wilayah Terpencil - Khalil Khalil; Ridwan Syah (Departement of Mathematics Education, 2024)
This research aims to identify and analyze effective energy infrastructure development strategies to improve accessibility and availability of energy in remote areas. Remote areas often face challenges in accessing adequate energy, which can hinder their social and economic development. Through a qualitative approach, this research explores various strategies that can be implemented to enhance energy accessibility and availability in remote areas. The SWOT analysis method is used to evaluate the strengths and weaknesses, as well as the opportunities and threats. The research findings suggest that the suitable strategy for energy infrastructure development in remote areas is to integrate existing strengths and opportunities. These findings are expected to provide valuable insights for decision-makers in designing sustainable and inclusive energy policies for remote areas, with a focus on improving energy infrastructure.